Comparison of the ruminal microbiome responses of temperate and tropically adapted beef steers to dietary supplementation with monensin - Thorn, Ross L.; Coffman, Lauryn E.; Rabalais Bass, Madeline M.; Long, Charles R.; Randel, Ronald D.; Welsh, Thomas H.; Somenahally, Anil C. (Frontiers in Animal Science, 2025)
The interactive responses of cattle genetics and the rumen microbiome (G×M) govern variations in the feed efficiency and methane emissions, which subsequently impact cattle productivity and their environmental footprint. Modulation of the rumen microbiome can be done through dietary supplementation, such as with the antimicrobial ionophore monensin, which offers a pathway to favorably alter metabolic outcomes. However, the limited data on breed-specific microbiome shifts in response to dietary changes restrict the understanding of the impacts of G×M on fermentation and nutrient utilization. The objective of the study was to determine the effect of a monensin-fed diet on the ruminal microbiome and the short-chain fatty acid (SCFA) profile of temperate and tropically adapted cattle breeds. A total of 10 steers each of the Angus, Brahman, and F1 (Angus × Brahman) breed types were fed forage ± a monensin ionophore supplement. Ruminal fluid samples were collected during four 21-day periods (one equilibrium and three treatments). At the conclusion of each period, the SCFAs were analyzed via gas chromatography. The microbiome profiles were analyzed through DNA extraction, quantitative PCR (qPCR) assays, and sequencing to evaluate the G×M interactions. SCFA analysis showed a decrease in the acetate/propionate ratio (p = 0.001) across all breed types under monensin treatment. However, breed type variations were evident, as the total SCFA concentrations were lower only in the Brahman steers that consumed monensin. The qPCR assays indicated significantly lower ruminal methanogen contents (mcrA gene; p < 0.01) and a reduced methanogen/prokaryote ratio (MPR; p < 0.001) in monensin-fed steers compared with the control. A treatment-by-breed interaction was observed for the fungi/prokaryote ratio (FBR; p = 0.003), with only F1 steers on the monensin diet showing a lower FBR than those on the control diet. The permutational analysis of variance (PERMANOVA) and beta diversity analyses demonstrated significant differences in the ruminal microbiome structure between the control and the monensin-treated groups for both prokaryotic and fungal communities. Several amplicon sequence variants (ASVs) within the genera Faecalimonas, Streptococcus, and Prevotella showed variable abundance among breeds in response to monensin treatment, confirming the influence of (G×M) interactions on the microbiome structure. This study established the potential of dietary supplementation with an antimicrobial ionophore (monensin) to modulate the rumen microbiome structure, alter the metabolic profiles, and reduce methanogens while emphasizing the need for breed-specific dietary strategies due to the influence of G×M interactions.